Commonalities and differences in carotid body dysfunction in hypertension and heart failure - Felippe, Igor S. A.; Del Rio, Rodrigo; Schultz, Harold; Machado, Benedito H.; Paton, Julian F. R. (My University, 2023)
Carotid body pathophysiology is associated with many cardiovascular-respiratory-metabolic diseases. This pathophysiology reflects both hyper-sensitivity and hyper-tonicity. From both animal models and human patients, evidence indicates that amelioration of this pathophysiological signalling improves disease states such as a lowering of blood pressure in hypertension, a reduction of breathing disturbances with improved cardiac function in heart failure (HF) and a re-balancing of autonomic activity with lowered sympathetic discharge. Given this, we have reviewed the mechanisms of carotid body hyper-sensitivity and hyper-tonicity across disease models asking whether there is uniqueness related to specific disease states. Our analysis indicates some commonalities and some potential differences, although not all mechanisms have been fully explored across all disease models. One potential commonality is that of hypoperfusion of the carotid body across hypertension and HF, where the excessive sympathetic drive may reduce blood flow in both models and, in addition, lowered cardiac output in HF may potentiate the hypoperfusion state of the carotid body. Other mechanisms are explored that focus on neurotransmitter and signalling pathways intrinsic to the carotid body (e.g. ATP, carbon monoxide) as well as extrinsic molecules carried in the blood (e.g. leptin); there are also transcription factors found in the carotid body endothelium that modulate its activity (Kruppel-like factor 2). The evidence to date fully supports that a better understanding of the mechanisms of carotid body pathophysiology is a fruitful strategy for informing potential new treatment strategies for many cardiovascular, respiratory and metabolic diseases, and this is highly relevant clinically.image Abstract figure legend The carotid body has been linked with the development of hypertension and heart failure in animals and humans. This review explores mechanisms of carotid body sensitisation across disease models. We ask whether these mechanisms are common or unique to distinct cardiovascular diseases; such knowledge could inform clinical treatment strategies. We propose that carotid body sensitivity increases progressively from health to hypertension and is maximal in heart failure and that there are both shared and distinct sensitisation mechanisms. This sensitisation is followed by an increase in systemic sympathetic outflow. It remains unknown whether the sensitised carotid body drives sympathetic overactivity or vice versa.image
Keywords: autonomic nervous system; blood flow; cardiovascular diseases; carotid body; heart failure; hypertension; sympathetic nervous system